THE SCOPE OF THE RIGHTS OF QUILOMBOLA COMMUNITIES IN BRAZIL: AN ANALYSIS OF DAU 3239 AT THE SUPREME FEDERAL COURT AND THE ALCÂNTARA COMMUNITIES CASE BEFORE THE INTER-AMERICAN COURT OF HUMAN RIGHTS (Social and Environmental Law Journal, 2025)
The pursuit of effectiveness in the rights of Quilombola Communities faces significant challenges due to the systemic failure of the state to protect, respect, and fulfill their human rights. On the international level, several documents provide special protection to these Communities, notably the International Labour Organization’s Convention No. 169 of 1989 and the United Nations Declaration on the Rights of Indigenous Peoples of 2007. It was only with the return to democracy, the enactment of the 1988 Federal Constitution, and the subsequent Decree No. 4,887 of 2003 that a protective legal framework was established in Brazil. This article aims to analyze the scope of national and international human rights norms concerning Quilombola Communities. To this end, it adopts a dual methodological approach. First, it conducts a literature review to assess the state of the art of national and international norms regarding Quilombola Communities, along with an analysis of their socioeconomic characteristics. Then, it proceeds to a case law analysis of two landmark decisions: DAU 3239, ruled by the Brazilian Supreme Federal Court in 2018, and the case before the Inter-American Court of Human Rights regarding the Communities of Alcântara, in which the Brazilian State was held accountable in 2024. The article concludes that rights violations against Quilombola Communities persist, and the reach of protective norms remains limited.
Keywords: Quilombola Communities; ILO Convention No. 169; DAU 3239; Alcântara Communities